Analysis Placement of Tsunami Vertical Evacuation Shelters Based on Number and Location (Case Study: Painan City) - Alfurqan, Ahmad; Ashar, Faisal (Universitas Negeri Padang, 2024)
Painan City is a city whose part of the area is located on the coast, so it is prone to tsunami disasters. This disaster is unpredictable and can occur at any time. Based on interview data with BPBD South Pesisir Regency, Painan City has 10 shelters ranging from; official shelters, buildings that are multifunctional as shelters, and natural shelters. The purpose of this study is to determine the range of services of the tsunami shelter in Painan City today. The research method used is a quantitative descriptive method. In this study, what was discussed was the evaluation of the number and location of existing shelters, as well as determining the location of planned or additional tsunami shelters, as well as to determine the coverage of areas that can be served by these shelters with the help of GIS applications. Based on the results of the analysis, it was found that the entire tsunami danger zone area of Painan City could be served by existing shelters, in a span of 26 minutes with a distance of 1,171.56 meters. This means that people in the tsunami danger zone can evacuate safely before the tsunami disaster comes.